The Islamic faith and best interests. (August 2019) - Two, Jessica; Curtice, Martin
Summary: This article reviews a 2017 Court of Protection case which assessed and decided issues relating to the Islamic faith and the Mental Capacity Act 2005. The case involved a 39-year-old Muslim man with learning difficulties. It centred on his ability to make decisions about two specific aspects of his faith – capacity for fasting and for the removal of pubic and axillary hair. The judgment describes how s.4 of the Act was applied in deciding these decisions under the doctrine of best interests. In doing so, it elucidates key principles which can be applied to similar cases of this and other faiths. Declaration of interest: None.